2019
DOI: 10.1002/cam4.2032
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation‐regulated and tumor‐suppressive roles of miR‐487b in colorectal cancer via targeting MYC, SUZ12, and KRAS

Abstract: Human colorectal cancer (CRC), characterized by its high morbidity and lethality, seriously threatens human health and lives. MicroRNA‐487b (miR‐487b) is currently reported to be aberrantly expressed in several tumors, but the detailed functions and underlying mechanisms of miR‐487b in CRC remain unclear. Here, we found that miR‐487b is downregulated in CRC cell lines and is markedly decreased in tumor specimens derived from CRC patients. MiR‐487b inhibits cell proliferation, migration and invasion and promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, miRNA-487b was shown to be downregulated in osteosarcoma CD133 positive cell lines [ 40 ] and inhibited osteosarcoma chemoresistance and metastasis [ 41 ]. The suppressive role of miRNA-487b was also indicated in colorectal cancer via targeting MYC, SUZ12 and KRAS [ 42 ]. On the other hand, in hepatocellular carcinoma, higher miRNA-487b expression was observed in the serum of HCC patients compared with healthy individuals, and was associated with poor prognosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, miRNA-487b was shown to be downregulated in osteosarcoma CD133 positive cell lines [ 40 ] and inhibited osteosarcoma chemoresistance and metastasis [ 41 ]. The suppressive role of miRNA-487b was also indicated in colorectal cancer via targeting MYC, SUZ12 and KRAS [ 42 ]. On the other hand, in hepatocellular carcinoma, higher miRNA-487b expression was observed in the serum of HCC patients compared with healthy individuals, and was associated with poor prognosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported miR-487b-3p as a tumor suppressor that inhibits osteosarcoma chemoresistance and metastasis by targeting ALDH1A3 [ 31 ]. miR-487b may participate in the interaction between GRM3 and TGF-β, and restrain the proliferation and metastasis of CRC cells [ 32 ]. Moreover, miR-487b-3p was also reported to be capable of preventing cell proliferation and differentiation in C2C12 myoblasts by targeting IRS1 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that abnormal miRNA expression in serum could be used as a biomarker for cancer. Work by Chen et al established that miR-487b was significantly downregulated in metastatic tissues compared with matched tumor tissues and that miR-487b can be regarded as a biomarker for early colorectal cancer diagnosis and a criterion to judge metastasis [ 24 ]. Another study by Wang et al illustrated that miR-487b played an oncogenic role in osteosarcoma progression via directly targeting TRAK2, which could advance the development of cancer treatment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%